2017
DOI: 10.1097/mrm.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases and sexually transmitted infection in a Hungarian prison

Abstract: Objective: The aim of the study was to assess the prevalence of the skin diseases, dermatological conditions, and sexually transmitted infections among male prisoners. Materials and methods: The medical data of 1800 inmates were analysed and a local sero-biological survey was performed in 2014. Moreover, after informed consent, dried blood spots were collected to identify recent hepatitis C virus (HCV) and HIV infections in case of homosexuality and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…a One MSM study [ 23 ] was excluded from the plots because of a high risk of bias (summary bias score = 0). b This number includes studies of people belonging to multiple (overlapping) risk groups (five such studies for PWID [ 39 , 47 , 61 , 62 , 66 ], four for prisoners [ 68 , 72 , 73 , 79 ], and seven for sex workers [ 81 , 82 , 84 - 88 ]). c One PWID study [ 66 ] was excluded from the forest plots because the original dataset was reported in another study [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…a One MSM study [ 23 ] was excluded from the plots because of a high risk of bias (summary bias score = 0). b This number includes studies of people belonging to multiple (overlapping) risk groups (five such studies for PWID [ 39 , 47 , 61 , 62 , 66 ], four for prisoners [ 68 , 72 , 73 , 79 ], and seven for sex workers [ 81 , 82 , 84 - 88 ]). c One PWID study [ 66 ] was excluded from the forest plots because the original dataset was reported in another study [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…b This number includes studies of people belonging to multiple (overlapping) risk groups (five such studies for PWID [ 39 , 47 , 61 , 62 , 66 ], four for prisoners [ 68 , 72 , 73 , 79 ], and seven for sex workers [ 81 , 82 , 84 - 88 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations